Formulation And Physical Quality Test Of Lip Balm Preparations From Yellow Sweet Potato Skin Extract (Ipomoea Batatas L.) - Ramadani, Novia Dwi; Safitri, Cikra Ikhda Nur Hamida (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
Formulation and testing of physical quality of lip balm preparation derived from sweet potato skin extract (Ipomoea batatas L). This study highlights the potential utilization of sweet potato skin, which is often discarded, as a valuable resource due to its high content of natural antioxidants and beneficial compounds. The extraction process was carried out to obtain skin extract, which was then formulated into a lip balm preparation at concentrations of 0.2% and 0.4%. This study was conducted using an experimental research method that aims to determine the activity of yellow sweet potato skin extract (Ipomoea batatas L.). The sampling technique in this study was purposive sampling. The skin used will meet the criteria of being clean, not moldy, not overgrown with fibers, the aroma remains fresh and distinctive, and does not smell bad. The results showed that the lip balm formulation with a concentration of 0.2% showed organoleptic test results, namely cacao aroma, semi-solid form, and brown color. The pH test results were 7 SNI standards, namely 4.5 - 8. The homogeneity test results were homogeneous preparations. The results of the spreadability test showed 4cm with a standard of 3-5 cm. So the conclusion from the concentration of 0.2% and 0.4% which showed good results was 0.2% because it met good physical quality standards.